IMF Research Bulletin, June 2007 - Spilimbergo, Antonio (IMF Research Bulletin; IMF Research Bulletin ;, 2007)
IMF research summaries on (1) oil market developments and the global economy (by Selim Elekdag), and (2) credit booms (by Marco Terrones); country study on India (by Helene Poirson); call for papers for November 2007 Jacques Polak Eighth Annual Research Conference; listing of contents of Vol. 54, Issue No. 2 of IMF Staff Papers; listing of recent IMF Working Papers; and listing of visiting scholars at the IMF during April-June 2007.